THU0415 Increased rigidity of salivary glands as indicated by sonoelastography is associated with reduced saliva production in primary sjÖgren's syndrome. (23rd January 2014) - Dejaco, C.; DeZordo, T.; Heber, D.; Lipp, R.; Lutfi, A.; Magyar, M.; Zauner, D.; Graninger, W.B.; Hermann, J.
Abstract : Background: Real-time sonoelastography (SElasto) is used to examine tissue elasticity. Chronic inflammation and fibrosis of major salivary glands leads to reduced saliva production in patients with primary Sjögren's syndrome (pSS). Objectives: To investigate the value of SElasto to detect pSS patients with reduced saliva production Methods: Prospective study on 38 pSS patients fulfilling the American-European consensus group criteria [mean age 58 years; 92% female; median duration of sicca symptoms 6 years, 65% histological sialadenitis] and 11 healthy controls. B-mode sonography and SElasto of parotid and submandibular glands was performed using a GE Logiq E9 ultrasound device. Parenchymal homogenicity, echogenicity, hypoechogenic areals, hyperechoic reflections and clearness of glandular borders were semiquantitatively scored (total score ranging from 0-48) (1). SElasto was used to examine the elasticity of glandular parenchyma and a semiquantitative rating was performed with 0=no, 1=up to 25%, 2=up to 50%, 3=up to 75% and 4=more than 75% hardened areas within the salivary gland. The total score ranged from 0 to 16. Clinical assessments were performed at the same day of sonographic evaluation and included: Saxon test, Schirmer test, Xerostomia inventory (XI), and the Ocular Surface Disease Index (OSDI). Statistical analysis was performed using SPSS program (v18.0) and the Mann-Whitney-U and Spearman rank correlation test were performed as appropriate. Interobserver variability of sonography was tested in 30% of pSS patients by intraclass correlation coefficient (ICC). Results: pSS patients had higher B-mode scores [median 25 (range 2.0-44.0) vs. 2.0 (0-8.0), p<0.001] and SElasto scores [6.0 (2.0-12.0) vs. 3.0 (1.0-4.0), p<0.001] than healthy controls. pSS patients showed a median salivary flow rate of 1.69 g/2min (range 0.31-3.79), a median moisture on the filter paper (Schirmer test) of 4.0mm/5min (0-50.0), a median XI of 27.5 (8.0-43.9) and an median OSDI of 43.8 (0-77.1). In pSS patients, an inverse correlation was found between the result of the Saxon test and SElasto score (corrcoeff -0.426, p=0.009), whereas B-mode ultrasound results were not associated with saliva production. Neither disease duration nor duration of sicca symptoms influenced ultrasound results. A good reproducibility of B-mode and SElasto results was found as indicated by an ICC of 0.926 (95%CI 0.565-0.983) and 0.934 (0.787-0.981), respectively. Conclusions: Increased rigidity of major salivary glands as demonstrated by SElasto in patients with pSS correlates with the impairment of saliva secretion. References: Hocevar A, Ambrozic A, Rozman B, Kveder T, Tomsic M. Ultrasonographic changes of major salivary glands in primary Sjogren's syndrome. Diagnostic value of a novel scoring system. Rheumatology 2005;44:768-72. Disclosure of Interest: None Declared